A Convenient Synthesis of 2, 3‐Dihydro‐4H‐thiopyrano[2, 3‐b]‐, ‐[2, 3‐c]‐, or ‐[3, 2‐c]pyridin‐4‐ones by the Reaction of the Corresponding 1‐(Chloropyridinyl)alk‐2‐en‐1‐ones with NaSH. Issue 4 (10th April 2013) - Kobayashi, Kazuhiro; Imaoka, Ayumi
Abstract 2, 3‐Dihydro‐4H‐thiopyrano[2, 3‐b]pyridin‐4‐ones 4 were prepared by a three‐step sequence from commercially available 2‐chloropyridine (1). Thus, successive treatment of 1 with iPr2NLi (LDA) and α, β‐unsaturated aldehydes gave 1‐(2‐chloropyridin‐3‐yl)alk‐2‐en‐1‐ols 2, which were oxidized with MnO2 to 1‐(2‐chloropyridin‐3‐yl)alk‐2‐en‐1‐ones 3. The reactions of 3 with NaSH⋅n H2O proceeded smoothly at 0° in DMF to provide the desired thiopyranopyridinones. Similarly, 2, 3‐dihydro‐4H‐thiopyrano[2, 3‐c]pyridin‐4‐ones 8 and 2, 3‐dihydro‐4H‐thiopyrano[3, 2‐c]pyridin‐4‐ones 12 were obtained starting from 3‐chloropyridine (5) and 4‐chloropyridine (9), respectively.